Legal Challenges of AI-Induced Copyright Infringement: Evaluating Liability and Dispute Resolution Mechanisms in Digital Era - Eviani, Nanda Yuniza; Maskun, Maskun; Faqi, Ahmad Fachri (Universitas Negeri Gorontalo, 2024)
The development of artificial intelligence (AI) has introduced unprecedented technological advancements and complex legal challenges, particularly in copyright infringement. The capability of the systems to replicate and disseminate copyrighted content without authorization raises questions about the adequacy of existing legal frameworks. Therefore, this research aims to explore the critical question of liability for AI-related copyright infringement, examining the responsibilities of developers, users, and systems. A comprehensive examination of relevant laws and regulations is carried out using a normative qualitative methodology. This is supported by case research and recent legal advancements, with a comprehensive comparison of relevant terms. Legal factors and dispute resolution methods applicable to AI-related copyright infringement are also considered. Due to the systems' autonomy, standard liability frameworks such as Digital Millennium Copyright Act (DMCA) cannot address AI-induced infringement. Meanwhile, a fault-based liability strategy that requires proof of purpose or negligence is suggested to improve accountability. This research reports the strengths and weaknesses of using dispute resolution mechanisms to solve copyright infringement. The results show that World Intellectual Property Organization (WIPO) dispute resolution provides a robust framework for resolving disputes after comparing regulations and mechanism.